Implementation of Bureaucratic Reform in Population Administration Services in the Digital Era - Karwur, Rener Brancho; L. Lumingkewas; Langkay, Jeane (JR Education, 2022)
The key to improving public services, specifically for service provider agencies, is to apply bureaucratic reform. This research aims to: 1) determine the application of bureaucratic reform from the aspect of bureaucratic behaviour in population administration services at the Department of Population and Civil Registration, Minahasa Regency, 2) determine the supporting and inhibiting factors in implementing bureaucratic reform from the aspect of bureaucratic behaviour in population administration services at the Department of Population and Civil Registration, Minahasa Regency. This research is descriptive qualitative research and the data are collected through observation, interviews and documentation. Furthermore, the informants of this research are the Head of Service, Head of Population Registration Services, and Head of Civil Registration Services, as well as the people who make use of the services of Population Administration. Generally, the results of this research are: 1) The application of bureaucratic reform from the aspect of bureaucratic behaviour in population administration services at the Department of Population and Civil Registration, Minahasa Regency, is still low. This is found according to the following data: (a) The Department of Population and Civil Registration of Minahasa Regency is not punctual and is considered slow in publishing population administration, (b) The Department of Population and Civil Registration of Minahasa Regency is deemed unfriendly and the employees still discriminate in providing services, (c) The employees do not have good communication skills with the community, therefore the socialization and counselling cannot run optimally. 2) There are 3 (three) supporting factors, which are: (a) Availability of